A competitive immunoassay for biotin detection using magnetic beads and gold nanoparticle probes. (15th January 2019) - Lin, Wen-Zhi; Chen, Yi-Hsiang; Liang, Chih-Kai; Liu, Cheng-Che; Hou, Shao-Yi
Highlights: A rapid and reliable competitive immunoassay for hapten detection is developed. The functionalized magnetic beads and gold nanoparticles as probes were used. The color change could be observed by the naked eye without any equipment. The detection limit was 2 pmol and could be completed within 15 min. It is useful for the detection of other haptens in food and abused drugs in urine. Abstract: Haptens are small molecules with low molecular weight that include biotin and many toxins in food. In this study, we used biotin as a model molecule for hapten detection. In this competitive immunoassay anti-biotin antibody-modified magnetic beads (Ab-MBs) and biotinylated thiol-DNA gold nanoparticles (biotin-GNPs) were used. The assay contains three reactions, the mixing of the sample and Ab-MBs, the capture of biotin-GNPs by Ab-MBs and the magnetic attraction. When biotin molecules were absent, the solution was transparent because biotin-GNPs bound to Ab-MBs which were caught by an external magnetic field. When biotin was present, the supernatant was red because the Ab-MBs bound to the analytes and the gold nanoparticles were still in solution. It was possible to complete all the operating steps in 15 min. The limit of detection (LOD) was 2 pmol. This rapid competitive-immunoassay has potential for application in detection of other haptens.